Riflessioni sulla politica monetaria internazionale - K. BRUNNER (Moneta e Credito, 2014)
The present article analyses the current state of international monetary policy and arrangements. The author first examines the nature of monetary arrangements guided by political institutions that are tempted to exploit the monetary system through the monopoly right to issue base money. The development of international institutions for controlling the monopoly right, the system of fixed exchange rates and the gold standard, and the eventual collapse of the Bretton Woods system are then reviewed. The recent development of the European Monetary System, its central issues and its prospects are then assessed. The author concludes that if the bureaucratic approach encouraged by the political process continues to disregard the one and only condition assuring a viable fix-rate system, that is sever constraints national monetary policies, the most likely outcome of the EMS will be a new series of speculative waves and an erratic monetary growth in the stronger currency areas with intermittent pressures on the stronger currency areas to accommodate the comparatively weaker area.